Application of sport psychology to mixed martial arts - Alexandro Andrade; Rodrigo Batalha Silva; Fábio Hech Dominski (2020)
This study, through a systematic review, analyzed scientific production concerning sport psychology in mixed martial arts. The review was conducted in accordance with the PRISMA statement, and the search was performed using the S ciELO, S cienceDirect , PsycInfo, and Web of Science databases . Of the 79 studies screened, eight satisfied the eligibility criteria, with explicit addressal of the topics of fear, aggression, emotional control, confidence, mental toughness, motivation, arousal, coping, rational emotive behavioral therapy for MMA athletes, fighting experience and MMA competition. Consequently, the scarce scientific production was found to evidence the need for further research in this modality. It is suggested that studies that investigate other variables of sport psychology such as mood, anxiety, and burnout.